Effect of chemical reaction in a third grade fluid in porous medium analyzed by unsteady magnetohydrodynamic couette - A.S. Idowu; S Usman (Journal of Applied Sciences and Environmental Management, 2018)
An analysis was carried out on unsteady magnetohydrodynamic (MHD) Couette third grade fluid in a porous medium in the presence of chemical reaction parameter. The Darcy’s law and Fick’s law of diffusion were introduced to stimulate the porosity and chemical reaction in the problem. The resulting flow problem was investigated and model of the problem in form of partial differential equations were obtained. He-Laplace method was used to obtain the solution of the equations and expressions for the velocity field, temperature and concentration distribution were given for each case. Graphical results for various interesting parameters were analyzed and presented.